Implementation of Nahwu Learning Media based on Articulate Storyline 3 for 2nd Grade Students at MA in MABIQ, Malaysia - Al-ansori, Hamdan Fauzan; Zaki, Muhammad; Nur, Ifa Rodifah (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
تستكشف هذه الدراسة تنفيذ وسائط تعلم النحو باستخدام برنامج Articulate Storyline 3 لطلاب الصف الثاني في المدرسة الإسلامية بمدينة مابيك، ماليزيا. تهدف البحث إلى معالجة الحاجة إلى أدوات تعليمية فعالة وجذابة لتعليم النحو للطلاب الصغار. باستخدام منهج البحث الوصفي الكيفي، تم جمع البيانات لفحص تأثير وسائط التعلم المنفذة على فهم الطلاب لمبادئ النحو باستخدام الملاحظة والمقابلة. تشير النتائج إلى نتائج إيجابية في تعزيز فهم الطلاب واهتمامهم بالموضوع. تسهم البحث في هذا المجال من خلال تقديم رؤى قيمة حول فعالية وسائط تعلم النحو التي تعتمد على التكنولوجيا. تختتم الدراسة بملخص للنتائج، مسلطة الضوء على الآثار المحتملة في تحسين تعليم اللغة العربية في المدارس الإسلامية. This study explores the implementation of Nahwu learning media using Articulate Storyline 3 for 2nd-grade students at MA in MABIQ, Malaysia. The research aims to address the need for effective and engaging educational tools for teaching Nahwu to young learners. Employing a descriptive qualitative research method, data were collected to investigate the impact of the implemented learning media on students' understanding of Nahwu principles. Results indicate positive outcomes in enhancing students' comprehension and interest in the subject. The research contributes to the field by providing valuable insights into the effectiveness of technology-based Nahwu learning tools. The study concludes with a summary of findings, highlighting the potential implications for improving Arabic language education in Islamic schools.